AN OPTIMIZATION OF A DIGITAL CONTROLLER FOR A STOCHASTIC CONTROL SYSTEM - Golinko, Igor; Drevetskiy, Volodymyr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
The article deals with the synthesis of an optimal digital controller for a stochastic plant. In order to optimize the control system, an integral quality criterion together with minimization of the controlled parameter variance that is offered here, besides the control actions the control objects are taken into account. Using the methods of optimization theory for a single-loop control system, the structure and parameters of the digital regulator are determined. The structure of the digital controller is analysed from the parameters of the quality criterion and the mathematical description of the control object. An example of the synthesis of a digital controller for an automatic control system for the air temperature at the output of the CV-P°2L°N-63B/F-N ceiling conditioner, which showed the efficiency of the digital controller when compensating for random disturbances, is given here. The obtained results are recommended to be used by the specialists on automation for the control system design as well as optimization of the existing ones.